Membangun Keluarga Sejahtera Melalui Pengembangan Model Pembelajaran pada Beberapa Desa Miskin di Provinsi Sumatera Selatan - Didi Tahyudin; Utsman Utsman; Yoyok Yoyok; Tri Agus S. (Universitas Negeri Malang, 2016)
This is the first of a follow up study that aims to obtain a model of teaching-learning activities for the poor families in the rural areas, poor in the sense of economy, education, religion, health, and environment. In order to enhance the people's knowledge all learning resources were coordinated, be they from government bodies as well as from private ones. Especially, this tudy (the first) concerns the concepts of teaching-learning activities, the approaches implemented in the models, the problems encountered, the learning potentials of the poor rural people, the priorities, the programs, and the learning strategies.